Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's solve the problem step-by-step by filling in the missing values for each polynomial factorization:
1. For the first polynomial [tex]\(x^2 + 2x - 15 = (ax + b)(cx + d)\)[/tex]:
[tex]\[ (1x - 3)(1x + 5) = x^2 + 5x - 3x - 15 = x^2 + 2x - 15 \][/tex]
From the calculation, we see that [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 5 \)[/tex].
2. For the second polynomial [tex]\(2x^3 + 6x^2 - 20x = 2x(ax + b)(cx + d)\)[/tex]:
[tex]\[ 2x(x - 2)(x + 5) = 2x(x^2 + 3x - 10) = 2x^3 + 6x^2 - 20x \][/tex]
From the calculation, we can deduce that [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 5 \)[/tex].
3. For the third polynomial [tex]\(9x^2 + 21x + 6 = (ax + b)(cx + d)\)[/tex]:
[tex]\[ (3x + 2)(3x + 1) = 9x^2 + 3x + 6x + 2 = 9x^2 + 21x + 6 \][/tex]
From the calculation, we find that [tex]\( a = 3 \)[/tex], [tex]\( b = 2 \)[/tex], [tex]\( c = 3 \)[/tex], and [tex]\( d = 1 \)[/tex].
Therefore, the complete table with the filled missing values is:
[tex]\[ \begin{tabular}{|c|c|c|c|} \hline a & b & c & d \\ \hline 1. & 1 & -3 & 1 & 5 \\ \hline 2. & 1 & -2 & 1 & 5 \\ \hline 3. & 3 & 2 & 3 & 1 \\ \hline \end{tabular} \][/tex]
1. For the first polynomial [tex]\(x^2 + 2x - 15 = (ax + b)(cx + d)\)[/tex]:
[tex]\[ (1x - 3)(1x + 5) = x^2 + 5x - 3x - 15 = x^2 + 2x - 15 \][/tex]
From the calculation, we see that [tex]\( a = 1 \)[/tex], [tex]\( b = -3 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 5 \)[/tex].
2. For the second polynomial [tex]\(2x^3 + 6x^2 - 20x = 2x(ax + b)(cx + d)\)[/tex]:
[tex]\[ 2x(x - 2)(x + 5) = 2x(x^2 + 3x - 10) = 2x^3 + 6x^2 - 20x \][/tex]
From the calculation, we can deduce that [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 5 \)[/tex].
3. For the third polynomial [tex]\(9x^2 + 21x + 6 = (ax + b)(cx + d)\)[/tex]:
[tex]\[ (3x + 2)(3x + 1) = 9x^2 + 3x + 6x + 2 = 9x^2 + 21x + 6 \][/tex]
From the calculation, we find that [tex]\( a = 3 \)[/tex], [tex]\( b = 2 \)[/tex], [tex]\( c = 3 \)[/tex], and [tex]\( d = 1 \)[/tex].
Therefore, the complete table with the filled missing values is:
[tex]\[ \begin{tabular}{|c|c|c|c|} \hline a & b & c & d \\ \hline 1. & 1 & -3 & 1 & 5 \\ \hline 2. & 1 & -2 & 1 & 5 \\ \hline 3. & 3 & 2 & 3 & 1 \\ \hline \end{tabular} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.